Dialektologi Bahasa Arab Pada Komunitas Tutur Arab Lokal (Alumni Ponpes Di Sulawesi Tenggara) - Rachmad Ramadhan (IAIN Madura, 2022)
In this study, the authors describe and explain the various types of dialect insertions that occur when Arabic is spoken by PBA IAIN Kendari students. Data were collected through qualitative and descriptive research, and the results are described in detail. PBA students at the IAIN Kendari campus are motivated by several ethnic groups in Southeast Sulawesi, including the Tolaki tribe whose language has the dialect insertion of deela, mi, ji, pokoknya, pucat, nah. Also, the Butonese and Wolio tribes whose languages have local dialects insertion ee, mi, mo kae, kaasi, and garaa. Bugis language has inserts ki, ka, ja, and pale. The Kabaena and Moronene tribes insert local dialects, namely na awu, amaa, nde e and baa. The Muna tribe has a local dialect with the insertion of kunae. Fields inserted using local dialects often occur in both formal and informal contexts. The insertion of local dialects used in communicative languages results in the form of transcoding and code-mixing. Transcoding that occurs can be in the form of a single sentence or dialogue. The implications of this research are expected to contribute to the use of Arabic which is still considered by many people to be difficult to use and understand until now. By inserting a local dialect, the use of Arabic will be easy to use and understand in the form of daily communication.Dialectology, Arabic, Code Mixing